Telecommunication networks - Iannone, Eugenio (Devices, circuits, and systems., 2012)
"The book outlines the current situation of the telecommunication network and the different alternatives for network evolution. It provides a systematic view of the network design problem, underlining its links between different aspects. It presents the engineering knowledge needed to construct a network evolution strategy, examines the elements influencing telecommunications network evolution and their interdependence, and supplies a complete review of the architecture alternatives. The content ranges from high level architectural elements to component physics, with a focus on enlightening the same problem from different points of view"--